Recovery of physical function and patient’s satisfaction after Total Hip Replacement (THR) surgery supported by a tailored guidebook - Fortina, M.; Carta, S.; Gambera, et al., D. (Acta Biomedica Atenei Parmensis, 2005)
Background and aim of the work: The purpose of this prospective study was to give a customized guide, describing the hospitalization period and the postoperative exercise program, to patients scheduled for total hip arthroplasty (THA) and to show its effectiveness on functional recovery and on patient’s satisfaction with the rehabilitation care and with the in-hospital discharge planning after surgery.Methods: This trial included 365 consecutive subjects with osteoarthritis who underwent THA at the Orthopaedic and Traumatology Clinic of Siena (Italy). The Harris Hip Score (HHS), a disease specific measure, was determined before and after surgery. Postoperative evaluations, associated with a Satisfaction Questionnaire, were carried out at the time of discharge and after 3 months. Results: The overall satisfaction level was very high, both at discharge (81±28) and at follow-up (90±17). The HHS results showed a significant (p≤0.05) improvement over time in patients with higher scores 3 months after surgery in comparison with baseline. Conclusions: Patients reported high levels of satisfaction at the 3 month postoperative follow-up and good levels at discharge. After surgery, the highest improvements were shown in bodly pain and physical function scores.The current study showed that a customized guide was well accepted by patients withTHA and satisfie their need of information. It was also effective in improving patient’s satisfaction and early recovery of physical function after surgery.